Examining the influence of travel motivation on travel expe-riences at marine tourism destinations in South Sulawesi - Yusuf, Maryam; Eppang, Buntu Marannu; Amalia, Intan Fauzia (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study focuses on the influence of travel motivation on travel experiences at marine tourism destinations in South Sulawesi. In the context of tourism development, particularly marine tourism, understanding travel motivations is crucial for enhancing the quality of destinations and tourist or travel experiences. The aim of this study is to analyze the relationship between tourists' travel motivations and their experiences at marine tourism destinations. This research employs a quantitative approach, with data collected through a questionnaire survey distributed to 220 respondents who have visited marine tourism destinations in South Sulawesi. The data analysis was conducted using a simple linear regression test to examine the relationship between travel motivation and travel experiences. The results of the study indicate that travel motivation has a positive and significant influence on travel experiences. Every increase in travel motivation contributes to an improvement in the unforgettable travel experience. The study also identifies several key motivational factors, including beach-based activities, natural beauty, and togetherness with family and friends. The conclusion of this study is that travel motivation is a crucial factor in shaping travel experiences at marine tourism destinations. The implications of this study emphasize the importance for destination managers to pay attention to and enhance tourists' travel motivational factors in order to create higher quality and more tourism experiences.